(untitled) (SCIENCE TIME JOURNAL, 2026)
This article conducts a comparative analysis of the ethno-cultural foundations and formation mechanisms of geographical terms (toponyms) in Uzbek and English languages. Employing a qualitative research methodology, the study investigates the etymological, morphological, and semantic aspects of selected place names from both linguistic systems. The research reveals that while both languages demonstrate universal tendencies in reflecting natural features, historical events, and human activities in their toponymy, significant ethno-cultural divergences shape their formation. Uzbek toponyms predominantly reflect Turkic heritage, rich influences from Arabic and Persian, and the historical nomadic and agrarian lifestyles of its people. In contrast, English toponyms showcase layers of Anglo-Saxon, Norse, and Norman French linguistic origins, interwoven with the socio-historical development of feudalism and exploration.